Zirconium hydrazides as metallanitrene synthons: release of molecular N2 from a hydrazinediido complex induced by oxidative N-N bond cleavage - Gehrmann, Thorsten; Lloret Fillol, Julio; Herrmann, Heike; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2013)
The N-N bond in the zirconium hydrazinediido(2−) complex [Zr(N2TBSNpy)(NNPh2)(py)] (1) is readily cleaved by one-electron oxidation. Reacting [Zr(N2TBSNpy)(NNPh2)(py)] (1) with 0.5 molar equiv of iodine led to the release of molecular N2 and yielded the mixed diphenylamido/iodo complex [Zr(N2TBSNpyNPh2)(I)] (2). Exposure of hydrazinediide 1 to an excess of iodine resulted in further oxidation of the diphenylamido ligand, yielding the diiodo complex 3 and tetraphenylhydrazine. Similar reactivity was observed in the reaction of 1 with diphenyl diselenide and diaryl disulfides, which reacted to give the corresponding diphenylamido/arylchalcogenido complexes [Zr(N2TBSNpyNPh2)(SePh)] (4a) and [Zr(N2TBSNpy)(NPh2)(SAr)] (Ar = Ph (4b), C6F5 (4c)) along with N2. The reactions were also carried out on an NMR scale with a 15Nα-labeled hydrazido complex (1-15N). In all cases a single 15N NMR resonance at 310.16 ppm, assigned to 15N2, indicated the formation of dinitrogen from the Nα atom in the hydrazide. A crossover labeling experiment employing a 1:1 mixture of 1 and 15Nα-labeled 1-15N revealed that the isotope distribution is, as expected, statistical 1:2:1 (14N2: 14/15N2: 15N2), which is consistent with a reaction pathway involving a dinuclear intermediate in the dinitrogen-forming step. Complex 1 reacted with N2O to give a mixture of two compounds, the bis(diphenylamido) complex 6 and the doubly bridged μ-oxo complex 7. In contrast, reaction of 1 with 1 molar equiv of pyridinium N-oxide only gave the doubly bridged μ-oxo complex 7 along with 2,2′-bipyridine and diphenylamine.
Gesehen am 29.01.2020
Im Titelzusatz ist die Zahl "2" tiefgestellt